PENGARUH PERCEIVED VALUE TERHADAP PURCHASE INTENTION YANG DIMEDIASI OLEH CONTINUANCE INTENTION PADA ONLINE GAME MOBILE LEGENDS:BANG-BANG - Dyah Wahyuning Utami (Jurnal Ilmiah Mahasiswa FEB, 2018)
Abstract: The rapid development of online games does not only make online games an entertainment but also now online games are included in a profitable business process. Not  a  few  online  game  players  are  willing  to  buy  virtual  products  sold  by  game publishers  and  are  interested  in  continuing  because  of  their  perception  of  virtual products and games. This study aims to determine the effect of perceived value and continuance intention on the user's online purchase intention Mobile Legends: Bang both influence directly or indirectly. This type of research is a causality explanation that explains the causal relationship between variables through hypothesis testing. The population of this research is all online users of the game Mobile Legends: Bang who have bought virtual products in the application. Sample selection was done by purposive sampling technique with a total of 196 respondents. The analysis tool used is SmartPLS3.0. The results of this study indicate that perceived value has an influence in increasing purchase  intention  and  continuance  intention.  Continuance  intention  also  has  aninfluence in increasing purchase intention. In addition, the results of the study prove thatcontinuance intention has an important role in mediating the relationship between perceived value and purchase intention. Keywords: Mobile Game, Online  game,  Virtual Product, Perceived Value,  PurchaseIntention, Continuance Intention. Abstrak: Perkembangan online game  yang pesat tidak hanya menjadikan online game sebagai hiburan semata namun juga saat ini online game termasuk kedalam proses bisnis yang menguntungkan. Tidak sedikit para pemain online game bersedia membeli produk virtual yang dijual publisher game   maupun berminat untuk berkelanjutan dikarenakan persepsi mereka terhadap produk virtual maupun permainan. Penelitian ini bertujuan untuk mengetahui pengaruh perceived value dan continuance intention terhadap purchase intention pengguna online game Mobile Legends:Bang-Bang baik pengaruh secara langsung maupun tidak langsung. Jenis penelitian ini adalah eksplanasi kausalitas yang menjelaskan hubungan kausal antara variabel-variabel melalui pengujian hipotesis. Populasi penelitian ini adalah seluruh pengguna online game Mobile Legends:Bang-Bang yang pernah membeli produk virtual dalam aplikasi. Pemilihan sampel dilakukan dengan teknik purposive sampling dengan total responden sejumlah 196 orang. Alat analisis yang digunakan adalah smartPLS 3.0. Hasil penelitian ini menunjukan bahwa perceived value memiliki pengaruh dalam meningkatkan purchase intention dan continuance intention